The role of teacher empowerment and reward systems in enhancing engagement through professional commitment - Mas Ning Zahroh; Rita Retnowati; Hendarman (Indonesian Journal of Educational Development (IJED), 2026)
This study examines the influence of teacher empowerment and rewards on teacher engagement through professional commitment. The research is motivated by the relatively low level of teacher engagement influenced by managerial and motivational factors within educational institutions. The objective is to analyze both direct and indirect effects of empowerment and reward systems on teacher engagement, with professional commitment serving as a mediating variable. A quantitative approach was employed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The respondents were secondary school teachers selected through purposive sampling. Data were collected through a structured questionnaire using a five-point Likert scale. The research instrument measured four constructs: teacher empowerment (autonomy, participation in decision-making, access to resources), reward (financial and non-financial compensation), professional commitment (dedication, loyalty, responsibility), and teacher engagement (vigor, dedication, absorption). Validity was assessed through convergent and discriminant validity, while reliability was tested using Cronbach's alpha and composite reliability. The findings indicate that teacher empowerment has a positive and significant effect on professional commitment and teacher engagement. Rewards demonstrate a positive but relatively weak effect on engagement. Professional commitment significantly mediates the relationship between empowerment and teacher engagement.